RIAK-RIAK POSMODERN DALAM CERPEN ABRACADABRA KARYA DANARTO - Syafruddin, Dudy (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2010)
Literature is a product of culture keeping abreast of human mind. Literary works is a means for the authors to express the social phenomenon in his life. The discourses about postmodernism in the second half of twentieth century, as a part of the story of human mind, was a profound interest for the Authors. In Indonesia, the postmodern discourse has come up in the 1960s. This paper involves the elements of Postmodernism in the short story â€œAbacadabraâ€ written by Danarto. The dominant elements in this short story are parody, fragmentary, and historiographic metafiction.